KetoABNO/NO(x) Co-Catalytic Aerobic Oxidation of Aldehydes to Carboxylic Acids and Access to α-Chiral Carboxylic Acids via Sequential Asymmetric Hydroformylation/Oxidation - Miles, Kelsey C. (Org Lett, 2016)
A method for aerobic oxidation of aldehydes to carboxylic acids has been developed using organic nitroxyl and NO(x) co-catalysts. KetoABNO (9-azabicyclo[3.3.1]nonan-3-one N-oxyl) and NaNO(2) were identified as the optimal nitroxyl and NO(x) sources, respectively. The mildness of the reaction conditions enable sequential asymmetric hydroformylation of alkenes/aerobic aldehyde oxidation to access α-chiral carboxylic acids without racemization. The scope, utility, and limitations of the oxidation method are further evaluated with a series of achiral aldehydes bearing diverse functional groups.